Overview Of Community Knowledge And Actions On The Dangers Of Rabies-Infected Dog Bites In Kineleosan Village, Kombi District - Jelita Mita Soputan; Lucyana Pongoh; Ilham Salam; Bertom Pajung; Vera Tombokan; Tony Pandaleke (CV. AFDIFAL MAJU BERKAH, 2026)
Rabies is a serious zoonotic disease caused by the Lyssavirus virus that attacks the central nervous system. The disease is still a threat, including in Kinaleosan Village where most of the community keeps dogs. The problems identified are the lack of public knowledge and preventive measures about rabies. There are still people who use traditional medicine such as lemon or chili pepper crushed after being bitten by a dog and do not immediately go to health facilities. The purpose is to find out an overview of the knowledge and actions of the people of Kinaleosan Village, Kombi District about the dangers of dog bites as rabies-transmitting animals. Using the methodology of quantitative descriptive research and the research population, all families who raise rabies-infected animals (dogs) in Kinaleosan Village as many as 235 families. Samples were taken from 148 families using the Slovin formula. Data were collected using questionnaires and analyzed using univariate analysis. The results showed that the characteristics of respondents' knowledge about the dangers of rabies-infected animal bites were mostly in the fairly good category, namely 75 respondents (50.7%). Meanwhile, the characteristics of public actions regarding the dangers of rabies-infected animal bites were mostly in the good category, namely 82 respondents (55.4%). The conclusion of this study is that the knowledge of the people of Kinaleosan Village about the dangers of rabies-infected animal bites is quite good (50.7%) and the community's actions are good (55.4%). It is recommended that the public continue to increase knowledge and increase actions regarding the dangers of rabies.